2010
DOI: 10.1039/c0an00539h
|View full text |Cite
|
Sign up to set email alerts
|

Imaging live cells grown on a three dimensional collagen matrix using Raman microspectroscopy

Abstract: Three dimensional collagen gels have been used as matrices for the imaging of live cells by Raman spectroscopy. The study is conducted on a human lung adenocarcinoma (A549) and a spontaneously immortalized human epithelial keratinocyte (HaCaT) cell line. The lateral resolution of the system has been estimated to be <1.5 μm making it possible to access the subcellular organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 48 publications
1
83
0
Order By: Relevance
“…The specific information contained in the Raman spectra can be related to changes to the physiology as a result of external stimuli [27][28][29][30]. The spatial resolution is of the order of 0.5-2 mm, providing access to the subcellular organisation of the cells at a molecular level [31][32][33][34][35]. In the case of FTIR spectroscopy, the spatial resolution is limited to some 5-10 mm in free space applications, although this can be reduced to 1-2 mm using high numerical aperture microscopic objectives, as in the case of Attenuated Total Reflection (ATR) FTIR microspectroscopy.…”
Section: Biophotonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific information contained in the Raman spectra can be related to changes to the physiology as a result of external stimuli [27][28][29][30]. The spatial resolution is of the order of 0.5-2 mm, providing access to the subcellular organisation of the cells at a molecular level [31][32][33][34][35]. In the case of FTIR spectroscopy, the spatial resolution is limited to some 5-10 mm in free space applications, although this can be reduced to 1-2 mm using high numerical aperture microscopic objectives, as in the case of Attenuated Total Reflection (ATR) FTIR microspectroscopy.…”
Section: Biophotonicsmentioning
confidence: 99%
“…Whereas dry samples are often required for FTIR analysis of tissue sections, Raman microspectroscopy is perfectly compatible with water immersion measurement which enhances the signal to background ratio and the collection of higher quality data [36,37]. The weak contribution from water offers the possibility to study cells in an aqueous environment and thus to keep them alive for the duration of the measurement [2,31,38], whereas the strong absorption from water means that such measurements in infrared can only be performed with high brightness sources such as synchrotrons [39].…”
Section: Biophotonicsmentioning
confidence: 99%
“…In principle, each principal component is a linear combination of the original variables for the simplified variables, therefore, var (PC1) ≥ var (PC2) ≥ (PCp), where var (PCi) represents the variance of PCi in the dataset. A scatter plot is generated from the data which shows groups of points representing variations within the dataset [25]. PCA was performed using Matlab (Mathworks, USA) following the different data analysis steps described in the previous section.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Furthermore, confocal operation is not available on many commercial spectrometers. Recent studies have demonstrated the benefits of using 3D collagen gels for Raman mapping of single live cells [39]. The substrate (collagen) contribution to the spectrum is shown to be negligible, reducing the requirement for substrate subtraction.…”
Section: Spectral Preprocessing: Raman Spectroscopymentioning
confidence: 99%